Unilateral Nasal Obstruction Causes Symptom Severity Scores Similar to Bilateral Nasal Obstruction - Weitzman, Rachel E.; Feng, Allen L.; Justicz, Natalie; Gadkaree, Shekhar K.; Lindsay, Robin W. (Facial Plastic Surgery, 2020)
The objective of this paper is to investigate the differences between unilateral and bilateral nasal obstruction with subjective symptomatology in nasal obstruction. This is a retrospective chart review of prospectively collected data of patients with nasal obstruction presenting to a facial plastic and reconstructive surgery clinic for evaluation and treatment. Patient demographics including age and gender were recorded along with nasal physical exam findings. These included internal valve narrowing (IVN), external valve narrowing, internal valve collapse, external valve collapse, and septal deviations (inferior and superior). Findings were reported for the left, the right, and both sides. Nasal valve and septal findings were recorded on 3- and 4-point Likert scales, respectively, for each side of the nose. A total of 1,646 patients were included in the study. On univariate analysis, a significant correlation was seen between Nasal Obstruction Symptom Evaluation (NOSE) scores and all individual exam findings (p < 0.001). On multiple linear regression, total, left, and right septal deviation (p < 0.001, p = 0.001, p = 0.007, respectively) and total, left, and right IVN (p < 0.001, p = 0.003, p < 0.001) were all predictive of an increased NOSE score. Patients with unilateral septal deviation or internal nasal valve narrowing have symptoms of nasal obstruction similar to those with bilateral nasal obstruction. Unilateral and bilateral septal deviation and internal nasal valve narrowing are predictive of having an increased NOSE score. Unilateral nasal obstruction should be recognized and treated as a cause for severe symptomatic nasal obstruction despite a normal contralateral nasal exam.
Keywords: nasal obstruction; septorhinoplasty; NOSE scale; nasal anatomic worksheet